The Portrait of Good Governance in the Framework of Religious andCultural Philosophy - Ferry Christian; Abdul Hamid Habbe; Syarifuddin Rasyid (www.amertainstitute.com, 2023)
This study aims to integrate the meaning of religious and cultural philosophy contained in the principles of goodgovernance. This research method is descriptive. Literature review to find meaning that is integrated with the principles of good governance from the perspective of religious and cultural philosophy in Indonesia. This research shows that religious philosophy provides a logical basis for religious thought in accordance with God's teachings. Government administrators are required to carry out the norms and laws taught in religion regarding God's commands and prohibitions, in managing and being accountable for the budget. Meanwhile, cultural philosophy has a moral responsibility, is reasonable and is based on cultural principles that can enhance human dignity. Cultural philosophy can be a guideline of behavior in implementing government so that it acts in accordance with the values, norms or laws that are in accordance with the cultural philosophy of each region.